Valuing Theory and Practice: Using a Portfolio Lens to Publish Research on Projects. Issue 3 (June 2023) - Davies, Andrew; MacAulay, Samuel C.
This article maps the contributions project scholars can make in management journals. Research on projects cuts across disciplinary boundaries, with scholars working in institutions with different norms, epistemologies, rewards, and selection environments. But this diversity can make it hard to know where to publish. We hope our map of the publication landscape—the "V diagram"—will help project scholars better understand and respect one another's diverse contributions and make conversations across the field flourish.